2021
DOI: 10.1002/anie.202101628
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Kinetic and Spectroscopic Signatures of Copper Sites for Direct Oxidation of Methane to Methanol

Abstract: Copper‐exchanged zeolites of different topologies possess high activity in the direct conversion of methane to methanol via the chemical looping approach. Despite a large number of studies, identification of the active sites, and especially their intrinsic kinetic characteristics remain incomplete and ambiguous. In the present work, we collate the kinetic behavior of different copper species with their spectroscopic identities and track the evolution of various copper motifs during the reaction. Using time‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(97 citation statements)
references
References 86 publications
9
85
1
Order By: Relevance
“…Among the known Cu-oxo active site structures reported so far, i.e. , [CuOH] + , [Cu 2 (μ-O)] 2+ , and [Cu 3 (μ-O) 3 ] 2+ , 28–32 the second has been characterized in Cu-MFI, -CHA, and -MOR zeolites. 31,33,34 Recent experiments 34 have shown that the Cu-MFI and -CHA zeolites activate CH 4 with activation enthalpies of 8.7 and 6.2 kcal mol −1 , respectively, which agree with the computational results reported by one of us (apparent E a,C–H = 8.8 and 6.8 kcal mol −1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the known Cu-oxo active site structures reported so far, i.e. , [CuOH] + , [Cu 2 (μ-O)] 2+ , and [Cu 3 (μ-O) 3 ] 2+ , 28–32 the second has been characterized in Cu-MFI, -CHA, and -MOR zeolites. 31,33,34 Recent experiments 34 have shown that the Cu-MFI and -CHA zeolites activate CH 4 with activation enthalpies of 8.7 and 6.2 kcal mol −1 , respectively, which agree with the computational results reported by one of us (apparent E a,C–H = 8.8 and 6.8 kcal mol −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…, [CuOH] + , [Cu 2 (μ-O)] 2+ , and [Cu 3 (μ-O) 3 ] 2+ , 28–32 the second has been characterized in Cu-MFI, -CHA, and -MOR zeolites. 31,33,34 Recent experiments 34 have shown that the Cu-MFI and -CHA zeolites activate CH 4 with activation enthalpies of 8.7 and 6.2 kcal mol −1 , respectively, which agree with the computational results reported by one of us (apparent E a,C–H = 8.8 and 6.8 kcal mol −1 ). 3,35 For Cu-MOR, on the other hand, resonance Raman spectroscopy has shown two similar Cu–O–Cu active sites with different reactivities, as indicated by two distinct measured activation enthalpies of 11.1 ± 0.5 and 14.7 ± 0.5 kcal mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the attribution of the active species in Cu zeolite catalysts remains controversial, unlike Fe zeolite catalysts, Cu zeolite catalysts can directly oxidize methane to methanol with O 2 [27,166,187,188]. Figure 11A demonstrates the proposed various copper active species formed inside the zeolite pores, such as monovalent copper oxygen species attached to one zeolite framework Al [189], a divalent copper-oxo cluster forming one extra framework µ-oxo bridge attached to two zeolite frameworks Al [189], a divalent copper-oxo cluster forming two extra framework µ-oxo bridges attached to two zeolite frameworks Al [188], and a divalent copper-oxo cluster forming three extra framework µ-oxo bridges attached to two zeolite frameworks Al [187,190,191]. Groothaert et al [192] reported that Cu-ZSM-5 could be directly reacted with methane by pretreating it in an oxygen atmosphere, realizing methanol production without contact between methane and oxygen.…”
Section: Copper-based Catalystmentioning
confidence: 99%
“…Cu- and Ni-exchanged zeolite socony mobil-5 (ZSM-5) zeolites , have been reported to catalyze the stepwise process of the CH 4 to CH 3 OH conversion. While various Cu-oxo active site structures, namely, [CuOH] + , [Cu 2 (μ-O) 2 )] 2+ , ,, [Cu 2 (μ-O)] 2+ , and [Cu 3 (μ-O) 3 ] 2+ , , have been proposed for Cu-ZSM-5, only the latter two have been extensively studied and suggested to favor the [Cu II 2 (μ-O)] 2+ and [Cu II 2 Cu III (μ-O) 2 (μ-O • )] 2+ electronic structures, respectively, although there is only little evidence for the existence of Cu 3+ . , As for Ni-ZSM-5, X-ray photoelectron spectroscopy and extended X-ray absorption fine structure measurements have shown that the active site involves Ni dimers with an indefinite oxo structure: either mono­(μ-O) or bis­(μ-O) . Nonetheless, theoretical efforts , have suggested bis­(μ-O)­dinickel as a potential candidate of the active site, considering that it facilely activates CH 4 with an activation barrier (16.3 kcal/mol) being consistent with the experimental value (19.9 kcal/mol) and its presence in complexes has been confirmed experimentally. These findings are different from Mo- and Cr-ZSM-5 catalysts, where monomer active sites are mainly formed and carburization and agglomeration tend to occur .…”
Section: Introductionmentioning
confidence: 99%